2015
DOI: 10.1021/acsami.5b05347
|View full text |Cite
|
Sign up to set email alerts
|

Nanodrug Formed by Coassembly of Dual Anticancer Drugs to Inhibit Cancer Cell Drug Resistance

Abstract: Carrier-free pure nanodrugs (PNDs) that are composed entirely of pharmaceutically active molecules are regarded as promising candidates to be the next generation of drug formulations and are mainly formulated from supramolecular self-assembly of drug molecules. It benefits from the efficient use of drug compounds with poor aqueous solubility and takes advantage of nanoscale drug delivery systems. Here, a type of all-in-one nanoparticle consisting of multiple drugs with enhanced synergistic antiproliferation ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
105
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(106 citation statements)
references
References 39 publications
1
105
0
Order By: Relevance
“…The combinatory drugs are mainly formulated from supramolecular self-assembly of drug molecules [105]. For example, DOX has the characteristic structure of a surfactant with the unsaturated anthracycline rings acting as the hydrophobic part and the saturated end of the ring system as a hydrophilic part.…”
Section: Nanoformulation-mediated Co-delivery Of Small-molecule Chmentioning
confidence: 99%
See 1 more Smart Citation
“…The combinatory drugs are mainly formulated from supramolecular self-assembly of drug molecules [105]. For example, DOX has the characteristic structure of a surfactant with the unsaturated anthracycline rings acting as the hydrophobic part and the saturated end of the ring system as a hydrophilic part.…”
Section: Nanoformulation-mediated Co-delivery Of Small-molecule Chmentioning
confidence: 99%
“…HCPT molecules are also hydrophobic; therefore, Zhao et al have shown that DOX could potentially be used for solubilizing and nanosizing HCPT through hydrophobic-hydrophobic interaction. Indeed, the water-solubility of HCPT was improved 50-fold after co-assembly with DOX [105]. The intermolecular forces or hydrophobic interaction between combinatory drug moieties were not only observed in these carrier-free pure nanodrugs but also when loading simultaneously in one polymeric micelles or particles (formulations described in section 3.1) [9, 106].…”
Section: Nanoformulation-mediated Co-delivery Of Small-molecule Chmentioning
confidence: 99%
“…Its nanocrystalline form, protected by surfactants or polymers, was obtainable in an anti-solvent precipitation process with water as an anti-solvent in previous studies Yang et al, 2015;Zhao et al, 2015). For instance, our recent study showed that a membrane emulsifier-assisted anti-solvent precipitation could be employed for integration of HCPT nanoneedles with a polymer layer to achieve comet-shaped microparticles with the sustained release property (Yang et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…SMND includes amphiphilic self-assembly nanodrug, [1][2][3] nanocrystallized or template-assisted nanodrug, [4][5][6][7] disulfide-induced self-assembled nanodrug, [8][9][10] and so on. It has attracted great interest as a desirable strategy, because of its unique properties in increased chemical stability and solubility, high drug loading, economical fabrication, relative "green" nanoformulation.…”
Section: Introductionmentioning
confidence: 99%